2015
DOI: 10.1128/iai.00141-15
|View full text |Cite
|
Sign up to set email alerts
|

Novel Paraoxonase 2-Dependent Mechanism Mediating the Biological Effects of the Pseudomonas aeruginosa Quorum-Sensing Molecule N -(3-Oxo-Dodecanoyl)- l -Homoserine Lactone

Abstract: cPseudomonas aeruginosa produces N-(3-oxo-dodecanoyl)-L-homoserine lactone (3OC12), a crucial signaling molecule that elicits diverse biological responses in host cells thought to subvert immune defenses. The mechanism mediating many of these responses remains unknown. The intracellular lactonase paraoxonase 2 (PON2) hydrolyzes and inactivates 3OC12 and is therefore considered a component of host cells that attenuates 3OC12-mediated responses. Here, we demonstrate in cell lines and in primary human bronchial e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 43 publications
2
33
0
Order By: Relevance
“…Neither the PON2-interaction with GLUT1 nor the PON2-mediated increase in GLUT1 activity was affected by the H114Q or H133Q mutation, which abrogates PON2 lactonase activity (Altenhofer et al, 2010; Horke et al, 2015), nor was there an effect of the commonly occurring polymorphism, S311C (Altenhofer et al, 2010) (Figure S6D and S6E). Furthermore, ectopic expression of GLUT1 restored the ability of PANC1 cells expressing PON2 shRNAs to form colonies in soft agar (Figure S6F).…”
Section: Resultsmentioning
confidence: 99%
“…Neither the PON2-interaction with GLUT1 nor the PON2-mediated increase in GLUT1 activity was affected by the H114Q or H133Q mutation, which abrogates PON2 lactonase activity (Altenhofer et al, 2010; Horke et al, 2015), nor was there an effect of the commonly occurring polymorphism, S311C (Altenhofer et al, 2010) (Figure S6D and S6E). Furthermore, ectopic expression of GLUT1 restored the ability of PANC1 cells expressing PON2 shRNAs to form colonies in soft agar (Figure S6F).…”
Section: Resultsmentioning
confidence: 99%
“…PON‐2 is a mitochondrial protein that plays an important role in modulating bacterial QS and host cell responses to bacterial homoserine lactone signaling molecules (48). We recently published that PPARγ modulates expression of PON‐2 (20); therefore, we wanted to determine the effects of PAO1 and 3O‐C12‐HSL on the expression of PON‐2 in epithelial cells.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have demonstrated that increased cellular calcium mediates degradation of PON-2 protein and mRNA. Since 3-oxo-C 12 -HSL can increase cytosolic calcium, it can be hypothesized that 3-oxo-C 12 -HSL may mediate changes in PPAR␥ and PON-2 levels by modulating the activity of key transcriptional factors (16,17,72,73). The induction of NF-B and interleukin-10 may also play a role in the inhibition of PPAR␥, as these are upregulated by 3-oxo-C 12 -HSL (74,75).…”
Section: Discussionmentioning
confidence: 99%
“…All three PON enzymes degrade oxidized lipids, protect against oxidative stress, and act to suppress inflammation. Paraoxonases have been shown to hydrolyze and thereby inactivate bacterial QS molecules, or N-acyl-homoserine lactones, such as 3-oxo-C 12 -HSL (13)(14)(15)(16)(17). In particular, PON-2 has the highest catalytic activity among the three PON proteins and is expressed in almost all human tissues (16).…”
mentioning
confidence: 99%